Computationally Optimized Broadly Reactive H2 HA Influenza Vaccines Elicited Broadly Cross-Reactive Antibodies and Protected Mice from Viral Challenges - Reneer, Z. Beau (J Virol, 2020)
Influenza viruses have caused numerous pandemics throughout human history. The 1957 influenza pandemic was initiated by an H2N2 influenza virus. This H2N2 influenza virus was the result of a reassortment event between a circulating H2N2 avian virus and the seasonal H1N1 viruses in humans. Previously, our group has demonstrated the effectiveness of hemagglutinin (HA) antigens derived using computationally optimized broadly reactive antigen (COBRA) methodology against H1N1, H3N2, and H5N1 viruses. Using the COBRA methodology, H2 HA COBRA antigens were designed using sequences from H2N2 viruses isolated from humans in the 1950s and 1960s, as well as H2Nx viruses isolated from avian and mammalian species between the 1950s and 2016. In this study, the effectiveness of H2 COBRA HA antigens (Z1, Z3, Z5, and Z7) was evaluated in DBA/2J mice and compared to that of wild-type H2 HA antigens. The COBRA HA vaccines elicited neutralizing antibodies to the majority of viruses in our H2 HA panel and across all three clades as measured by hemagglutination inhibition (HAI) and neutralization assays. Comparatively, several wild-type HA vaccines elicited antibodies against a majority of the viruses in the H2 HA panel. DBA/2J mice vaccinated with COBRA vaccines showed increase survival for all three viral challenges compared to the wild-type H2 vaccines. In particular, the Z1 COBRA is a promising candidate for future work toward a pandemic H2 influenza vaccine. IMPORTANCE H2N2 influenza has caused at least one pandemic in the past. Given that individuals born after 1968 have not been exposed to H2N2 influenza viruses, a future pandemic caused by H2 influenza is likely. An effective H2 influenza vaccine would need to elicit broadly cross-reactive antibodies to multiple H2 influenza viruses. Choosing a wild-type virus to create a vaccine may elicit a narrow immune response and not protect against multiple H2 influenza viruses. COBRA H2 HA vaccines were developed and evaluated in mice along with wild-type H2 HA vaccines. Multiple COBRA H2 HA vaccines protected mice from all three viral challenges and produced broadly cross-reactive neutralizing antibodies to H2 influenza viruses.